Green initiatives among dwellers in Ashby Road Flat Ipoh / Siti Nurbaya Abu Bakar - Abu Bakar, Siti Nurbaya (2022)
Low-cost flats pose many challenges in implementations of any green initiative programmes by the city. Residents in low-cost housing seems to have unique social lifestyle that favors informal activities and social interactions and which is similar to the village. This research aims to investigate formal and informal green initiatives among dwellers in flats at Ashby Road, Ipoh. A case study approach was adopted to achieve the research aim. The research approach uses qualitative method of field observation and semi structured interview to accumulate data on green initiative activities and their impacts to the dwellers. The interview involved 10 residents from 10 blocks of the flats who are involved in green initiative activities. This semi structured interview data were analyzed using a thematic qualitative data analysis. Most dwellers who joined the informal green initiative experienced more impact in their livelihood. Some others joined the activities to fulfil their leisure time as a hobby.